Determination of the Optimum Annealing Temperature in the Production of CuO Nanoparticles with Antimicrobial Properties - Oruc, Cigdem; Celik-Bozdogan, Aysegul; Kurt-Gur, Gunseli; Asikoglu-Bozkurt, Asuman; Lus, Huseyin Murat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2022)
A copper oxide (CuO) nanoparticle, a transition metal oxide with a wide variety of easy production methods, can be used as an antimicrobial agent against various types of bacteria. CuO nanoparticles were produced by the sol-gel method, annealed and structural characteristics and antimicrobial properties of these particles were investigated. Single-phase monoclinic of CuO nanoparticle formation was confirmed by X-ray powder diffraction (XRD) spectra, FTIR techniques, differential scanning calorimetry with thermal gravimetry were used to characterize. It was determined that annealing in the temperature range of 150-900 degrees C affects both structure and particle size and antimicrobial characteristics. CuO nanoparticle size was found to be between about 25-70 nm at 150-900 degrees C annealing temperature, which does not have this wide temperature range in the literature. These results were supported by the TEM micrographs of the CuO nanoparticles observed at 150 degrees C and 900 degrees C. The antimicrobial activity of the synthesized nanoparticles was tested with the discffdiusion assay against Staphylococcus aureus, Escherichia coli, Agrobacterium tumefaciens, and yeast Pichia pastoris. The antimicrobial properties of the nanoparticles first increased and then decreased and disappeared as the annealing temperature increased. The antimicrobial properties of CuO nanoparticles disappeared at 750 degrees C and above, while the maximum antimicrobial effect was at 300 degrees C. The inhibition zones were examined and similar results were observed in all tested microorganisms.
Keywords: Agrobacterium tumefaciens; annealing effect; antimicrobial properties; CuO nano-particles; Escherichia coli; sol-gel method; Staphylococcus aureus; OXIDE NANOPARTICLES; METAL; NANOMATERIALS; WATER; CEO2; Science & Technology - Other Topics; Materials Science; Physics